2014
DOI: 10.1017/s1751731113002425
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid composition of tissue protein is affected by the total sulfur amino acid supply in growing pigs

Abstract: The factorial approach to assess the amino acid (AA) requirements of pigs is based on the assumption that the AA composition of body protein is constant. However, there are indications that this assumption may not be valid because the AA composition of body protein can be affected by the AA supply. The extent to which different tissues are affected by an AA deficiency is unknown. The objective of this study was to investigate the effect of feeding pig diets with a deficient or sufficient total sulfur AA supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
5
17
0
Order By: Relevance
“…The proportion of type I fibers varied from less than 2 % in white SM to more than 50 % in RM, and type IIB fibers from less than 20 % in RM to more than 80 % in LM and white SM, in agreement with the existing literature [28]. The His concentration was lower in RM than in other muscles, which is in agreement with previous data from our laboratory [17]. This is also consistent with the higher concentration of carnosine in LM than in the mixed slow-and fast-twitch oxidative trapezius muscle [1].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The proportion of type I fibers varied from less than 2 % in white SM to more than 50 % in RM, and type IIB fibers from less than 20 % in RM to more than 80 % in LM and white SM, in agreement with the existing literature [28]. The His concentration was lower in RM than in other muscles, which is in agreement with previous data from our laboratory [17]. This is also consistent with the higher concentration of carnosine in LM than in the mixed slow-and fast-twitch oxidative trapezius muscle [1].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous work from our laboratory [16,17] and reported differences between LM and the semimembranosus muscle in pigs [46]. Because fiber types have different contractile and metabolic properties [39], differences in AA composition among muscles may be related to differences in the composition of fiber types.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Cai et al (2010) and Conde-Aguilera et al (2014) reported high contents of glutamic acid, aspartic acid, lysine, leucine and arginine in the longissimus dorsi muscle of pigs, which is similar to the current results. Evans & Bowman (1992) showed that Cr supplementation in rat diets led to an increased uptake of glucose and amino acids in the skeletal muscle.…”
Section: Resultssupporting
confidence: 91%